Pengaruh Online Customer Review Dan Harga Open Trip Terhadap Keputusan Pembelian Konsumen PT Jalan Dulu Asia - Nabilah, Jihan; Suhardoyo; Kuswara, Heri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Rapid development of technology and information has changed consumer behavior. Utilization of the internet is used as a means for transactions and determining purchasing decisions. This study aims to analyze the influence of online customer reviews and open trip prices on consumer purchasing decisions at PT Jalan Dulu Asia Bandung. The method used is quantitative using multiple linear regression analysis, and hypothesis testing through SPSS version 26, Sampling using the purposive sampling method (samples with certain criteria) and data collected through questionnaires with a sample of 100 respondents. The results of the study are proven by the results of the t-test of the online customer review variable (X1) obtained t count 10.393> t table 1.984 and price (X2) obtained t count 7.118 > t table 1.984. The results of the simultaneous F test of online customer reviews (X1) and prices (X2) on consumer purchasing decisions (Y) obtained F count 142.383 > F table 3.090 and the results of the simultaneous determination coefficient calculation (R²) obtained a value of 0.746 (74.6%) which indicates that the variables online customer reviews (X1) and prices (X2) simultaneously influence consumer purchasing decisions (Y), while the rest is 25.4%. The results of the study indicate that online customer reviews and open trip prices have a positive and significant effect on consumer purchasing decisions at PT Jalan Dulu Asia Bandung.